2021
DOI: 10.3390/rs13050894
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New UAV Magnetic Prospecting Tool for Volcano Monitoring and Geohazard Assessment

Abstract: The use of unmanned aircraft vehicles (UAVs) in volcanological contexts is a key challenge in studying volcanoes and improving efficiency in the monitoring of volcanic activity. The coupling of ground and satellite measurements has been reinforced at an intermediate scale thanks to UAV measurements. Along with carrying out visible and infrared measurements, UAVs can conduct geophysical measurements for more in-depth studies. Magnetic field measurements are a powerful tool in volcanic contexts for (i) mapping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…However, installing multiple magnetometers is difficult and requires a larger drone. Larger drones create more magnetic noise and, therefore, suitable drone size is an important consideration [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, installing multiple magnetometers is difficult and requires a larger drone. Larger drones create more magnetic noise and, therefore, suitable drone size is an important consideration [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that landmines may be detected by attaching one magnetometer to a small UAV (sUAV) [ 37 , 38 ]. The conditions for detecting landmines involve measuring magnetic anomalies and adjusting for the distance between the landmine and the sUAV [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we focus on the UAV applications dealing with magnetic field measurement or mapping, the research is mainly focused on the cost-effective airborne magnetic surveys for industrial and geoscientific applications [ 7 ] in exteriors. These applications not only involve geological and geophysical mapping [ 8 ], which can be performed thanks to the UAVs on a regional scale [ 9 ], but can also be used to perform magnetic surveys for geothermal exploration [ 10 ], volcano monitoring [ 11 ], and related geohazard assessments [ 12 ] for the evaluation of factors affecting gully headcut locations [ 13 ]. The magnetic sensors placed on the UAV boards can be used for mineral exploration and mining operations [ 14 ] or for the detection and identification of the orphaned oil and gas wells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…UAV magnetic surveys can cover a wider range with a higher efficiency compared with the traditional terrestrial magnetic surveys, and are also easy to operate, have a low-cost, and have a good safety profile compared with manned aircraft magnetic surveys [3]. In addition, UAV-based magnetic surveys can also be carried out in areas that are difficult to access or that would pose a potential hazard to operators (e.g., near active volcanoes), which means that some gaps in traditional magnetic surveys can now be studied [4,5].…”
Section: Introductionmentioning
confidence: 99%